Quality of Life in the Regions - Results for German Counties - Thiess Büttner; Alexander Ebertz (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2007)
In order to assess differences in living conditions across German regions we apply the hedonic approach of Rosen (1979) and Roback (1982) to land-price and wage differences across Germanys counties. Employing a recent survey of more than half a million Germans on a wide range of social and political issues we confirm that differences in amenities give rise to substantial differences in land prices. With regard to wages, however, we find only little effects of amenities. Relying on the land-price effects we assess the quality of life in each of the German counties and provide a comprehensive ranking.
Keywords: R22; R32; 330; Land prices; regional income differentials; hedonic regression; quality of life; compensating wage differentials